Sacred Groves: Myths, Beliefs, and Biodiversity Conservation—A Case Study from Western Himalaya, India - Singh, Sushma; Youssouf, Mudasir; Malik, Zubair A.; Bussmann, Rainer W. (International Journal of Ecology, 2017)
Religious and traditional beliefs, cultural mores, and practices play a crucial role in the conservation of environment and biodiversity. The present paper describes a case study of two sacred groves in Western Himalaya. Sacred groves (SGs) are patches of land that are communally protected with religious zeal. A preliminary survey was conducted in these SGs to study their role in biodiversity conservation. The data collected included the general information regarding the SGs and the associated deity, nearest human habitation, access to them, and their floral and faunal diversity. Ethnomedicinal property of plants was collected from the indigenous communities. Many taboos are associated with both the SGs, which help in managing resources well through ritual representation. Different festivals are organized, where the local communities reaffirm their commitment to the forest and the deity. Sacred groves, in general, are a valuable tool of biodiversity conservation. But people’s changing attitudes, erosion of traditional beliefs, and human impact have caused degradation of sacred groves over the years. Their conservation would not be possible without the active participation of the local people. By improving their living standards and by giving benefits of conservation to them, long-term conservation goals in these SGs can be achieved.